A Highly Sensitive Kinetic-Spectrophotometric Method for the Assay of Carbamazepine in Pure and Commercial Tablet - Sarmad B. Dikran; Faeza H. Zankanah (College of Pharmacy University of Baghdad, 2017)
The study aimed to recommend a new spectrophotometric-kinetic method for determination of carbamazepine (CABZ) in its pure form and pharmaceutical forms. The proposed procedure based on the coupling of CABZ with diazotized sulfanilic acid in basic medium to yield a colored azo dye. Factors affecting the reaction yield were studied and the conditions were optimized. The colored product was followed spectrophotometrically via monitoring its absorbance at 396 nm. Under the optimized conditions, two method (the initial rate and fixed time (10 minute)) were applied for constructing the calibration graphs. The graphs were linear in concentration ranges 2.0 to 18.0 Âµg.mL-1 for both methods. The proposed was applied successfully in the determination of CABZ in its commercial formulations. Keywords: Kinetic, Spectrophotometry, Carbamazepine, Pharmaceutical formulations